Speakers and oratorical art of the Kirghiz people (Eurasian Journal of Philology Science and Education, 2018)
This article describes the types of speakers, oratory art, as well as its development in the Kyrgyz people. The Kirghiz as well as in other Turkic-speaking peoples have a wide variety of genres of oral literature. Legends, fairy tales, proverbs-proverbs, oratorical art occupy a large place in Kyrgyz folklore. Oratory is a literary heritage of the Kyrgyz people for many centuries. Oratory art is born and developed in connection with pressing problems, such as management, regulation of human relations in society. The essence of the discussion, the nature of the speaker, the role and place in society and methods of oratory have long been the basis of their research.